Simplify the expression. Give the exact value in simplified form. Rationalize any demoninators.

6 times the square root of 6

over

-4 times the square root of 30

### 1 Answer | Add Yours

`(6xxsqrt(6))/(-4xxsqrt(30))`

`sqrt(yx)=sqrt(y)xxsqrt(x)`

`sqrt(30)=sqrt(5xx6)=sqrt(5)xxsqrt(6)`

Thus

`(6xxsqrt(6))/(-4xxsqrt(30))=(6xxsqrt(6))/(-4xxsqrt(5)xxsqrt(6))`

`=6/(-4sqrt(5))`

`=(3xxsqrt(5))/(-2xxsqrt(5)xxsqrt(5))`

`=(3xxsqrt(5))/(-10)`

`=(-3xxsqrt(5))/10`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes